Spatial gravity wave characteristics obtained from multiple OH(3–1) airglow temperature time series. (December 2015) - Wachter, Paul; Schmidt, Carsten; Wüst, Sabine; Bittner, Michael
Abstract: We present a new approach for the detection of gravity waves in OH-airglow observations at the measurement site Oberpfaffenhofen (11.27°E, 48.08°N), Germany. The measurements were performed at the German Remote Sensing Data Center (DFD) of the German Aerospace Center (DLR) during the period from February 4th, 2011 to July 6th, 2011. In this case study the observations were carried out by three identical Ground-based Infrared P-branch Spectrometers (GRIPS). These instruments provide OH(3-1) rotational temperature time series, which enable spatio-temporal investigations of gravity wave characteristics in the mesopause region. The instruments were aligned in such a way that their fields of view (FOV) formed an equilateral triangle in the OH-emission layer at a height of 87 km. The Harmonic Analysis is applied in order to identify joint temperature oscillations in the three individual datasets. Dependent on the specific gravity wave activity in a single night, it is possible to detect up to four different wave patterns with this method. The values obtained for the waves' periods and phases are then used to derive further parameters, such as horizontal wavelength, phase velocity and the direction of propagation. We identify systematic relationships between periods and amplitudes as well as between periods and horizontal wavelengths. A predominant propagation direction towards the East and North-North-East characterizes the waves during the observation period. There are also indications of seasonal effects in the temporal development of the horizontal wavelength and the phase velocity. During late winter and early spring the derived horizontal wavelengths and the phase velocities are smaller than in the subsequent period from early April to July 2011. Highlights: Spatial gravity wave parameters derived from OH(3-1) temperature time series. Relationships between wave parameters and predominant directions were identified. An indicated seasonal effect of the derived parameters is discussed.